Pregnancy After Cerebral Bypass for Moyamoya Disease. (1st September 2019) - Church, Ephraim W; Qaiser, Rabia; Bell-Stephens, Theresa E; Chow, Eric; Han, Summer; El-Sayed, Yasser Y; Steinberg, Gary K
Abstract: INTRODUCTION: Moyamoya disease (MMD) disproportionately affects young to middle age women. Vascular neurosurgeons are often needed to counsel women regarding pregnancy following bypass for MMD, but there is a paucity of data. We set out to examine neurological and obstetric outcomes in an extensive cohort of MMD patients who had pregnancies following cerebral revascularization at the Stanford Medical Center. METHODS: We identified all patients who underwent cerebral bypass for MMD and later became pregnant from 1990 through 2018. Some of these patients also had pregnancies prior to bypass, and we examined these pregnancies as well. We performed a chart review and a brief telephone survey to identify obstetric complications, transient ischemic attack (TIA), and stroke. Neurological and obstetric outcomes were compared to published rates. We also compared pre- and postbypass pregnancy complication rates using logistic regression techniques. RESULTS: There were 71 pregnancies among 56 women with mean age 30.5. Among 59 postbypass pregnancies, there were 5 (8%) perinatal TIAs. There were no magnetic resonance imaging (MRI) confirmed strokes or strokes with residual deficits. Among 12 prebypass pregnancies, there were 3 (25%) TIAs and 2 (17%) MRI-confirmed strokes. There were no hemorrhagic complications in either group. In the multivariable logistic regression analysis, performing cerebral revascularization prior to pregnancy versus postpregnancy was associated with lower odds of perinatal stroke or TIA (OR 0.13, P = .007). The overall rate of cesarean delivery was 39%. CONCLUSION: We present neurological and obstetric outcomes in a large cohort of MMD patients. These data indicate that postbypass pregnancy is accompanied by low complication rates. There were no ischemic or hemorrhagic strokes among postbypass, pregnant MMD patients. Obstetric complications were low overall. We recommend a close collaboration between the vascular neurosurgeon and the obstetrician regarding medical management, including blood pressure goals and continuation of aspirin.